Profil dan Teknik Bedah Hemoroid di RS Lhokseumawe dan Aceh Utara 2020–2021 - Dayanti Nuroazi Utari; Muhammad Sayuti; Zubir Zubir (Inovasi Kesehatan Global, 2025)
Hemorrhoids are dilation and inflammation that occurs in the arterial-venous plexus in the anal canal which functions as a valve to prevent flatus and fluid incontinence. This study aims to determine the characteristics of hemorrhoid patients and their surgery techniques in Lhokseumawe city hospital and North Aceh district. This type of research is descriptive observational with total sampling method and analyzed univariately using statistical software with a total sample of 119 hemorrhoid patients who have met the inclusion criteria. Based on the research, it was found that the incidence of hemorrhoids was dominated by early elderly age, male gender experienced more hemorrhoids, namely 60.5%. the most types of hemorrhoids were internal hemorrhoids 88.2% Most of the degree 3, namely as much as 44.7%. The most widely used surgical technique in hemorrhoid patients is the hemorrhoidectomy technique, totaling 95.8%. Respondents who experienced anemia were 63%. The erythrocyte index picture found is a hypochromic microcytic picture.